2014
DOI: 10.1111/ijcp.12518
|View full text |Cite
|
Sign up to set email alerts
|

Is there a link between overactive bladder and the metabolic syndrome in women? A systematic review of observational studies

Abstract: Objectives: To conduct a systematic review to determine whether there is an association between metabolic syndrome (MetS) and lower urinary tract symptoms (LUTS) or overactive bladder (OAB) in women. Methods: We systematically reviewed English language observational studies on the effect of MetS (or component factors) on the presence of OAB or LUTS in women. We searched PubMed, Web of Science and The Cochrane Library with no date restrictions, checked reference lists and undertook citation searches in PubMed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 82 publications
(140 reference statements)
3
66
0
2
Order By: Relevance
“…In line with these clinical findings, bladder dysfunction has also been reported in rat models of metabolic syndrome (Chung et al 2013;Lee et al 2008). In line with others (Bunn et al 2015;Kirby et al 2010), we conclude that metabolic syndrome apparently exhibits a more robust association with LUTS than its individual components of dyslipidemia and diabetes.…”
Section: Clinical Associations Between Atherosclerosis Risk Factors Asupporting
confidence: 91%
See 1 more Smart Citation
“…In line with these clinical findings, bladder dysfunction has also been reported in rat models of metabolic syndrome (Chung et al 2013;Lee et al 2008). In line with others (Bunn et al 2015;Kirby et al 2010), we conclude that metabolic syndrome apparently exhibits a more robust association with LUTS than its individual components of dyslipidemia and diabetes.…”
Section: Clinical Associations Between Atherosclerosis Risk Factors Asupporting
confidence: 91%
“…A recent systematic review of associations between female LUTS and metabolic syndrome or components thereof identified four studies exploring such associations for hyperlipidemia, of which three found no significant association and one increased odds for OAB in women with hyperlipidemia (Bunn et al 2015). Among similar studies in men, one comparing 120 men with and 285 without LUTS, total, HDL, and LDL cholesterol as well as triglyceride levels measured after an overnight fast did not differ significantly between groups (Rohrmann et al 2005).…”
Section: Clinical Associations Between Atherosclerosis Risk Factors Amentioning
confidence: 99%
“…Sleep disturbance has also been shown to be a significant risk factor for cardiovascular and metabolic disorders (e.g., obesity, diabetes), 3 and the literature available to date appears to support a link between metabolic disorders and OAB. 21 …”
Section: Discussionmentioning
confidence: 99%
“…A link between OAB and metabolic syndrome, or components of metabolic syndrome such as diabetes, may explain some of the cardiovascular and neurological symptoms. 25 In a large population-based study, Coyne et al (2011) showed that men and women with LUTS/OAB had higher prevalence of hypertension, diabetes, heart disease, arthritis, and neurologic conditions compared to individuals with no or minimal LUTS/OAB symptoms. 7, 8 We noticed high rates of hypertension (37%), diabetes (8%) and stroke/transient ischemic attack (8%) among our OAB cohort, however the rates were not statistically different from controls (33%, 3% and 7% respectively), due to small sample size.…”
Section: Discussionmentioning
confidence: 99%